Intermittent Vagal Nerve Stimulation-Associated Vocal Fold Movement Impairment. (August 2022) - Yan, Jennifer; Ongkasuwan, Julina; Lambert, Elton M.
Objectives: Implanted vagal nerve stimulators (VNS) are an accepted therapy for refractory seizures. However, VNS have been shown to affect vocal fold function, leading to voice complaints of hoarseness. We present a case of intermittent VNS-related vocal fold paralysis leading to dysphonia and dysphagia with aspiration in a pediatric patient. Methods: This is a case report of a patient at a tertiary hospital evaluated in pediatric swallow and voice clinics. Patient and mother gave verbal consent to be included in this case report. Results: Indirect laryngeal stroboscopy was performed demonstrating full vocal fold mobility with VNS off and left vocal fold paralysis in lateral position and glottic gap with VNS on. Voice measures were performed demonstrating decreased phonation time, lower pitch, and decreased intensity of voice with VNS on. Flexible endoscopic evaluation of swallowing demonstrated deep penetration alone with VNS off and deep penetration with concern for aspiration with VNS on. Conclusions: While the majority of cases of vocal fold movement impairment associated with VNS have been noted to have a medialized vocal fold with VNS activation, we describe a case of intermittent vocal fold lateralization associated with VNS activation with resultant voice changes and aspiration.